First reported stranding of a dwarf minke whale, Balaenoptera acutorostrata (lacépède, 1804), on the coast of Ceará, Northeastern, Brazil - Meirelles, Ana Carolina Oliveira de (2011)
This paper reports the first stranding of a dwarf minke whale, Balaenoptera acutorostrata, in the State of Ceará, Northeastern Brazil. The animal stranded in advanced state of decomposition on Tabuba Beach (03º38’08”S, 38º42’21”W) on July, 2005. The specimen identification was based on the analyses of skull morphological features and morphometrical characters. This is the second documented record of a dwarf minke whale stranding in latitudes lower than 05º00’S.